Detection of Escherichia coli Bacterial Contamination on Cutlery at Warung Lesehan Around Nologaten Yogyakarta - Hanifah Viki Tri Utami (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2023)
Background: Diarrhea is among the second-highest disease cases in the Special Region of Yogyakarta. Escherichia coli infection most often causes diarrhea. Escherichia coli infection can be through food and drinks with low hygiene and sanitation. Escherichia coli bacterial contamination indicates hygiene and sanitation in food preparation.Purpose: This study aims to detect Escherichia coli contamination on cutlery at Warung Lesehan around NologatenYogyakarta.Methods: This type of research is qualitative, with a cross-sectional study design conducted in March-May 2022 in Nologaten Village, Sleman, Yogyakarta. The samples in this study were cutlery in the form of plates, which were determined using an accidental sampling technique of 14 plate samples. Sampling for Escherichia coli examination was carried out using a plate swab technique. The Escherichia coli examination was conducted at the Yogyakarta Health and Calibration Laboratory Center. The results of the research were carried out by univariate data analysis.Results: The results of this study showed that there were 4 (28.6%) positive samples contaminated with Escherichia coli and 10 (71.4%) negative samples contaminated with Escherichia coli.Conclusions: Escherichia coli contamination exists on four cutlery at Warung Lesehan around Nologaten Yogyakarta.